Consumer Perceptions of Electric Motorcycle Adoption Factors in Indonesia: A Descriptive Analysis Across Income, Gender, and Vehicle Ownership Segments - Tauriq Aldila Firdaus; Yuniaristanto Yuniaristanto; Retno Wulan Damayanti (Dinasti Research, 2026)
Indonesia's massive conventional motorcycle (CM) market presents both a challenge and an opportunity for electric motorcycle (EM) adoption. While government subsidies and supportive policies have been introduced, adoption rates remain persistently low, highlighting the need for a deeper understanding of consumer perceptions. This study provides a descriptive portrait of consumer perceptions toward electric motorcycle adoption based on a cross-sectional survey of 786 respondents across major Indonesian cities. Nine constructs were examined: Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, Brand Trust, and Purchase Intention. Descriptive statistics and segmentation analyses were conducted across income, gender, and vehicle ownership groups. Findings indicate that Effort Expectancy and Brand Trust were the most favorably rated constructs, while Habit recorded the lowest means, reflecting psychological attachment to conventional motorcycles. Public charging infrastructure availability emerged as the weakest facilitating factor. Income showed the clearest demographic differentiation, with higher-income respondents reporting more positive perceptions across virtually all constructs. Gender differences were minimal, and current EM owners consistently reported more favorable perceptions than non-owners. These findings provide a granular baseline to inform targeted strategies for policymakers, manufacturers, and marketers seeking to accelerate sustainable mobility transition in Indonesia.